Editorial: developing medicinal plant extracts commercially: the importance of extraction and fractionation - Brendler, Thomas; Chua, Lee Suan; Abdullah, Luqman Chuah; Yam, Mun Fei (Frontiers Media, 2023)
The use of botanical drugs is integral to healthcare practices of indigenous populations. From there stems“combined with a growing interest in and popularity of using botanical medicines and supplements in everyday healthcare and wellbeing“the steady increase in demand for readily available herbal products that are efficacious, safe and of high quality (Smith et al., 2022). Botanical medicines and supplements are manufactured into a variety of dosage forms, ranging from traditional infusions and tinctures, powders, gummies, capsules and tablets all the way to sophisticated delivery systems to enhance bioavailability and/or determine time and location of release, such as inhalates or orodispersible films and melts. Additionally, botanicals are incorporated into foods, cosmetics, and personal care products.